Evaluation of the sperm migration capacity of crossbred dairy cattle bull semen vis-à-vis field fertility trials - Bhatia, Himanshu; Singh, Prahlad; Sidhu, S S (The Indian Journal of Animal Sciences, 2012)
Crossbred dairy cattle bulls (6) were subjected to semen evaluation study twice a week for sperm migration capacity in bovine cervical mucus (BCM) and poly-acrylamide gel (PAG). Cervical mucus from respective cows subsequently inseminated with same semen, was tested for sperm penetration test (SPT). PAG was prepared according to standard procedures and stored at 4°C till further use. Different grades of PAG (2% and 3%) were examined for transparency, spinbarkeit, pH and visible gelification before using for sperm migration assay. Field fertility trials based on pregnancy outcome by assigning 10 cows/bull were conducted simultaneously to BCM penetration test (BCMPT) and PAG-SPT. 2% PAG was better in assessing sperm penetration distance than 3% PAG, however, the values differed nonsignificantly. Sperm migration in BCM was better than sperm migration in PAG, and differences were significant for semen of respective bulls. The pregnancy outcome from the bull (FC-1207) having maximum sperm penetration distance (SPD) in BCM (fresh semen, 38.63 ± 0.26 mm/20 min; extended semen, 37.39 ± 0.19 mm/20min; frozen semen, 36.85 ± 0.21 mm/20min), 2% PAG (fresh, 37.44 ± 0.54 mm/20min; extended, 36.60 ± 0.34 mm/20 min; frozen, 35.89 ± 0.44 mm/ 20min) were around 58.53%, whereas, bull showing lower values of SPD in BCM and 2% PAG had lower pregnancy outcome. Six bulls under study indicated a lot of individual variation for SPD and pregnancy outcome, highlighting lower pregnancy outcome for bulls showing less SPD of sperm from fresh and frozen semen. Positive correlations were exhibited between different penetration tests and pregnancy outcome as well as between BCMPT and PAG-SPT. PAG can thus substitute for bovine cervical mucus and for assessing the sperm migration ability of various bulls used for breeding programme beforehand. Positive correlations between these tests and pregnancy outcome based on field fertility trials indicates importance of these tests for evaluating the fertility of bulls particularly with PAG-SPT before subjecting them to field evaluation.